Actinomycetoma caused by Gordonia westfalica: first reported case of human infection. (March 2020) - Gueneau, R.; Blanchet, D.; Rodriguez-Nava, V.; Bergeron, E.; Soulier, M.; Bestandji, N.; Demar, M.; Couppie, P.; Blaizot, R.
Abstract: Bacteria of the genus Gordonia are rarely involved in human infections. We report here the case of a 30-year-old man from Guinea Buissau with mycetoma of the foot. 16S DNA sequencing after surgical biopsy identified Gordonia westfalica . To our knowledge, this is the first report of human infection caused by G. westfalica .